Legal Protection of the Torem Tree (Manilkara Kanosiensis) as an Endemic Plant - Narwadan, Theresia Nolda Agnes; Labetubun, Muchtar Anshary Hamid; Fataruba, Sabri (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: Yamdena Island, part of the Tanimbar Islands, Maluku, holds unique biodiversity, including the endemic Torem Tree (/Manilkara kanosiensis/). This tree has important ecological value as an ecosystem buffer, economic value for local communities through the use of its fruit and wood, and cultural value related to traditional traditions and rituals. However, the Torem Tree faces serious threats from deforestation, land conversion, and unsustainable exploitation, exacerbated by climate change. Inadequate legal protection status is a crucial issue.Purposes of the Research: This study aims to analyze and evaluate the effectiveness of legal protection of the Torem Tree as an endemic plant on Yamdena Island.Methods of the Research: The research method used is normative law with a statutory and conceptual approach. Data is obtained from related laws and regulations, legal literature, and relevant documents. Data analysis is carried out through legal interpretation, comparative analysis, and legal synthesis.Results Main Findings of the Research: The findings of the study show that the existing legal framework has not effectively protected the Torem Tree. The legal loophole lies in the lack of specific regulations that recognize and protect the endemic status of the Torem Tree, as well as weak enforcement of the law against related violations. This study concludes the need to strengthen legal protection through comprehensive revision of laws and regulations, increased effective supervision and law enforcement, and increased active participation of local communities in conservation efforts. Policy recommendations include the establishment of a clear legal status for the Torem Tree, the development of a sustainable management plan based on local wisdom, and increasing public awareness of the importance of the conservation of the Torem Tree for the sustainability of the ecosystem and the welfare of the Yamdena community.